The Effect of Semantic Mapping and Brainstorming as Prewriting strategies on Developing the English Writing Ability and Motivation for Learning of the Tenth Grade students in Dubai Educational Zone - Abu baker, Sahar Omar (2015)
The purpose of this study was to examine the effects of an educational program for teaching the skill of writing, using semantic mapping and brainstorming as prewriting strategies on developing students' writing ability and evaluating the role of these strategies that may play in increasing students' motivation for learning. The population of the study consisted of all the tenth grade students in the public schools of Dubai Educational Zone year 2014-2015. The sample of the study consisted of (74) students (males and females). The main question was about the effect of two pre-writing strategies: semantic mapping and brainstorming on students' writing ability and motivation for learning. To answer this, the researcher proposed a writing program and a motivation for learning questionnaire. Afterwards, each experiment group was taught according to one of the two teaching writing strategies (semantic mapping or brainstorming); while the control groups were taught in the traditional way. The findings of the study indicated significant differences in favour of the experimental groups taught in general and semantic mapping in particular according to the educational writing program. In the light of these findings, the researcher ended the research with some relevant recommendations to be utilized for further researches.